Sodium fast reactors with closed fuel cycle - Raj, Baldev, 1947-2018; Chellapandi, P.; Vasudeva Rao, P. R. (CRC Press, 2015)
Sodium Fast Reactors with Closed Fuel Cycle delivers a detailed discussion of an important technology that is being harnessed for commercial energy production in many parts of the world. Presenting the state of the art of sodium-cooled fast reactors with closed fuel cycles, this book: offers in-depth coverage of reactor physics, materials, design, safety analysis, validations, engineering, construction, and commissioning aspects. Features a special chapter on allied sciences to highlight advanced reactor core materials, specialized manufacturing technologies, chemical sensors, in-service inspection, and simulators. Addresses design essentials with a focus on reactor assembly including core and coolant circuits, fuel handling, instrumentation and control, energy conversion, and containment systems. Provides design codes and standards with sufficient background information to ensure a solid understanding of the underlying mechanics. Supplies guidelines for concept selection, design, analysis, and validation.